Semiotika Desain Oblong Dagadu Djokdja - Tinarbuko, Sumbo (Jurnal ILMU KOMUNIKASI, 2006)
Abstract: In the name of fun and being made without any burden the product of Dagadu Djokdja freely rockets in the air, and yet keep staying on the earth. The uniqueness as well as the strength of this product is, firstly, that it gives aesthetic to the daily subject, simple, even trivial, and sometimes, forgotten already. For that reason the design section counts on the graphic design aspect as its deadly weapon in order to convey and to reveal the approved themes. Secondly, it emphasizes the aspect of specific graphic design by joining the localism, humor, and the sense on fun into the pop art world in order to create attractiveness as the selling point of the product. Thirdly, it chooses the manufacture image instead of craft, both by material and by any other graphic design element. Fourthly, the distinctiveness as well the characteristic of all T-shirt designs of Dagadu Djokdja are the use of poster approach (poster style).